Data, Science and Cities. - Sarkar, Somwrita; Farid, Reza (Palgrave Macmillan, 2020)
This chapter focusses on the key role played by big data and data science in evaluating scientific theories of the city, in helping us understand the real time city, and in helping us to plan better functioning cities. A crucial message is that big data on cities and data science are complementary and parallel to urban design and urban planning. While the focus in urban design and planning is on the “making” of cities, the focus in data science is developing the “understanding” of the processes and forms that make up a city. Finally, a scientific understanding should provide the evidence and information base on which planning and design decisions are shaped and enacted.
Keywords: Digitalisierung; Stadtplanung; Datenanalyse; Stadtforschung; Big Data; Data Science